Aquaporins: another piece in the osmotic puzzle - Alleva, Karina Edith (2012)
Osmolarity not only plays a key role in celluar homeostasis but also challenges cell survival. The molecular understanding of osmosis has not yet been completely achieved, and the discovery of aquaporins as molecular entities involved in water transport has caused osmosis to again become a focus of research. The main questions that need to be answered are the mechanism underlying the osmotic permeability coefficients and the extent to which aquaporins change our understanding of osmosis. Here, attempts to answer these questions are discussed. Critical aspects of the state of the state of knowledge on osmosis, a topic that has been studied since 19th century, are reviewed and integrated with the available information provided by in vivo, in vitro and in silico approaches.